Design of interfaces to promote the bonding strength between dissimilar materials. (April 2022) - Ding, Yuchen; Abdullah, Arif M.; Dunn, Martin; Yu, Kai
Abstract: A fundamental challenge during the manufacturing of hybrid polymeric structures is to promote the bonding strength between dissimilar materials. While there are existing studies to achieve tough interfaces by developing new chemistry or using adhesive layers, they are performed in an ad-hoc manner and are challenging to be incorporated into automatic advanced manufacturing processes ( e.g., multi-material additive manufacturing). In this study, instead of relying on the new chemistry or adhesive layers, we investigate the influences of interfacial geometry on the bonding strength between soft and stiff polymers with a chemical dissimilarity. The interfacial geometry under consideration involves two-level hierarchical structures with different patterns (Strip, Buzzsaw, or Zigzag) in each level. Uniaxial tensile tests are conducted to characterize the enhancements in the interface compared to a flat interface. Finite element analysis is then applied to capture the experimental results and assist to understand the mechanism of interfacial properties' enhancement. Parametric studies based on the computational model also reveal design considerations to promote the mechanical strength of fabricated components. The understanding and computational tools developed in this study would provide valuable design guidelines in terms of interfacial geometry and material selections for optimal mechanical performances of hybrid multifunctional polymeric products.